Multiakad dalam Transaksi Syariah Kontemporer pada Lembaga Keuangan Syariah di Indonesia - Maulana, Hasanudin (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2011)
The development of Islamic finance in Indonesia affects the development of Islamic finance products dynamically. The agreement in Islamic transactions underwent a variety ofinnovations from several existing agreements in mu‘âmalah jurisprudence concept. One of them is the concept of multi-agreements in a transaction. Transactions with these multiagreement forms exist in almost Islamic products currently. This article also discusses various scholarly opinions with all variants of the concept multi-agreements.DOI: 10.15408/aiq.v3i1.2518